Novel n-3 Immunoresolvents: Structures and Actions - Dalli, Jesmond (Nature Publishing Group, 2013)
Resolution of inflammation is now held to be an active process where autacoids promote homeostasis. Using functional-metabololipidomics and in vivo systems, herein we report that endogenous n-3 docosapentaenoic (DPA) acid is converted during inflammation-resolution in mice and by human leukocytes to novel n-3 products congenerous to D-series resolvins (Rv), protectins (PD) and maresins (MaR), termed specialized pro-resolving mediators (SPM). The new n-3 DPA structures include 7,8,17-trihydroxy-9,11,13,15E,19Z-docosapentaenoic acid (RvD1(n-3 DPA)), 7,14-dihydroxy-8,10,12,16Z,19Z-docosapentaenoic acid (MaR1(n-3 DPA)) and related bioactive products. Each n-3 DPA-SPM displayed protective actions from second organ injury and reduced systemic inflammation in ischemia-reperfusion. The n-3 DPA-SPM, including RvD1(n-3 DPA )and MaR1(n-3 DPA), each exerted potent leukocyte directed actions in vivo. With human leukocytes each n-3 DPA-SPM reduced neutrophil chemotaxis, adhesion and enhanced macrophage phagocytosis. Together, these findings demonstrate that n-3 DPA is converted to novel immunoresolvents with actions comparable to resolvins and are likely produced in humans when n-3 DPA is elevated.